2004
DOI: 10.1080/0267303042000221945
|View full text |Cite
|
Sign up to set email alerts
|

Selective migration in Swedish distressed neighbourhoods: can area‐based urban policies counteract segregation processes?

Abstract: Like many other Western European governments, the Swedish government has launched an area-based urban policy in order to solve the problems of the distressed neighbourhoods in the largest cities. However, in the current policy it is not clear whether the primary aim is to address the problems of individuals, or if the aim is to change the market position of the distressed areas. The intervention might be successful in terms of assisting residents in finding jobs and better education, but that might not improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 22 publications
7
94
0
7
Order By: Relevance
“…We make neighbourhoods operational using the Swedish SAMS (Small Area Market Statistics) areas. These have been used to approximate neighbourhoods in previous studies using the same GeoSweden database (for example Andersson and Bråmå, 2004;Galster et al, 2008). We have excluded all SAMS (herein referred to as neighbourhoods) from the choice set of neighbourhoods with a population of less than 50 inhabitants (mostly commercial and industrial areas).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We make neighbourhoods operational using the Swedish SAMS (Small Area Market Statistics) areas. These have been used to approximate neighbourhoods in previous studies using the same GeoSweden database (for example Andersson and Bråmå, 2004;Galster et al, 2008). We have excluded all SAMS (herein referred to as neighbourhoods) from the choice set of neighbourhoods with a population of less than 50 inhabitants (mostly commercial and industrial areas).…”
Section: Methodsmentioning
confidence: 99%
“…Neighbourhood characteristics are thus reproduced (see e.g. Friedrichs, 1991;Andersson and Bråmå, 2004 for studies on the reproduction of poverty neighbourhoods). Bailey and Livingstone (2007) have shown that the primary drivers of vacancy rates are demographic mix and housing stock characteristics (see also van Ham and Clark, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mobility can form part of a 'spiral of decline', wherein higher turnover leads to dwelling vacancies and a further decline in a neighbourhood's reputation (Prak & Priemus, 1986). High turnover, and especially selective migration, can be both a signal of, and a mechanism for, low attractiveness and a bad reputation (Andersson & Brama, 2004).…”
Section: Reputation Studies In Recent Neighbourhoods Researchmentioning
confidence: 99%
“…Andersson and Bråmå (2004) consider status change and selective migration, finding that the latter reinforces existing patterns of segregation as expected. Crucially, however, their work does not consider the absolute scale of the impact of migration flows on segregation.…”
mentioning
confidence: 99%